If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = 14x + -13x + 8 Reorder the terms: 36 = 8 + 14x + -13x Combine like terms: 14x + -13x = 1x 36 = 8 + 1x Solving 36 = 8 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 36 + -1x = 8 + 1x + -1x Combine like terms: 1x + -1x = 0 36 + -1x = 8 + 0 36 + -1x = 8 Add '-36' to each side of the equation. 36 + -36 + -1x = 8 + -36 Combine like terms: 36 + -36 = 0 0 + -1x = 8 + -36 -1x = 8 + -36 Combine like terms: 8 + -36 = -28 -1x = -28 Divide each side by '-1'. x = 28 Simplifying x = 28
| 8-x=2x+8 | | 15x=-60 | | 7x-1=7(x+6) | | 2x-y-z=5 | | 0.01(x+6)-0.06=0.01(7x+6) | | 4(5y+4)=9(y+8) | | 4x^4+4x^2+4=0 | | 17x-7y=11 | | 8x+25=3x+50 | | r+19=25 | | 5=-2-x | | 10x+24=4x+126 | | a+2b=180 | | 3.9x=2.2x+10.2 | | 3.5x-20=2.4x+12 | | 254-7x=38x+24 | | x-21=-9 | | y/5+3/8=y/8-3/8 | | 19+k=-2 | | 4n/3-2/7=50/21 | | -2x-4x+13=-4-5x-10 | | b-18=-6 | | b*b*b=0 | | 5x/8-7=18 | | 2+s=2 | | 14n-9+3(5n)=20 | | 3x+(-3y)+(-10x)+y= | | x/7-3=-7 | | 2x+2=7x-7 | | 14n-9+(5n)=20 | | x/7-5=-9 | | 9x-12=5x+19 |